Commercial honey in the Philippines II. physical and chemical properties - Tilde, Aurora C.; Payawal, Pacifico C. (1992)
The 72 honey samples collected throughout the country were subjected to different chemical analyses.

About 46% of the total samples registered a reducing sugar content below the recommended minimum. Forty-five percent of the wild honey types and 48% of the A. mellifera honey have reducing sugar content below 60%. Most of the honey standards have reducing sugar content falling within the recommended value of not less than
65%.

Apis mellifera honey tend to have lower moisture content (range: 15-22%) than the wild honey types (16.2-33.1%).

Diastase activity is generally low or lacking in wild honey types. Average and range of diastase activity are 14.02 and 5.98-31.09, respectively, in A. mellifera hon-eys, and 8.2 and 3.3-13.50, respectively, in the wild honey types.

HMF content is generally high in both wild honey types and A. mellifera hon-eys. Average values are above the recommended minimum of 80 mg/kg honey.
Keywords: Honey; Chemical properties